2021
DOI: 10.1111/1744-9987.13716
|View full text |Cite
|
Sign up to set email alerts
|

The scientific basis and future of lipoprotein apheresis

Abstract: Lipoprotein apheresis plays a vital role in the management of the severe hyperlipidemias that predispose to atherosclerosis. Determinants of efficacy are the acute reduction in lipoproteins achieved by each apheresis procedure, their frequency, and the fractional catabolic rates and hence pool sizes of low‐density lipoprotein (LDL) or lipoprotein (a) (Lp(a)) of the patient being treated. A useful criterion of the efficacy of apheresis plus lipid‐lowering drug therapy is the decrease in the interval (time‐avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Besides lifestyle and nutritional measures, primary therapies are of pharmacological nature, among those statins and the recently introduced PCSK‐9 inhibitors [ 4 , 5 , 6 ]. In patients with intolerance to available drugs or in those not sufficiently responding to drug therapy, the use of extracorporeal blood purification techniques is considered to lower blood levels of LDL‐cholesterol and Lp(a) [ 7 , 8 , 9 , 10 ]. These include various apheresis techniques, which aim to lower blood levels of atherogenic LDL‐cholesterol and Lp(a) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides lifestyle and nutritional measures, primary therapies are of pharmacological nature, among those statins and the recently introduced PCSK‐9 inhibitors [ 4 , 5 , 6 ]. In patients with intolerance to available drugs or in those not sufficiently responding to drug therapy, the use of extracorporeal blood purification techniques is considered to lower blood levels of LDL‐cholesterol and Lp(a) [ 7 , 8 , 9 , 10 ]. These include various apheresis techniques, which aim to lower blood levels of atherogenic LDL‐cholesterol and Lp(a) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Im Gegensatz dazu kann bei HoFH durch medikamentöse Lipidsenker meist keine ausreichende LDL-C-Senkung erreicht werden. Bei diesen Patienten, deren Zahl aber sehr begrenzt ist, spielt die LA eine zentrale Rolle; sie sollte bereits im Kindesalter gestartet werden und kann sogar während einer Schwangerschaft erfolgen (wo orale Lipidsenker in aller Regel kontraindiziert sind) 22 . Medikamentös sind neben den üblichen Lipidsenkern auch Lomitapid und Evinacumab für die HoFH zugelassen.…”
Section: Künftige Rolle Der Lipoproteinapherese Vor Dem Hintergrund D...unclassified
“…So far, there is no approved pharmacological approaches to reduce Lp(a) to the level which can benefit ASCVD. 317 However, niacin, mipomersen and PCSK9 inhibitors show a certain effect on lowering Lp(a), although these effects may not translate into substantial clinical benefits. 318 320 The recently concluded phase 2 trial of pelacarsen demonstrated significant Lp(a) lowering capacity.…”
Section: Cholesterol-related Diseases and Interventionsmentioning
confidence: 99%